Freedom and borders: A theory of citizenship for the age of globalization: Bingley: Emerald Publishing Limited. DOI: https://doi.org/10.1108/9781801179904 ISBN: 978-1-80117-990-4 (electronic) / 978-1-80117-994-2 (print) - Sa'diyah, Halimah (Universitas Negeri Yogyakarta, 2026)
Freedom and Borders: A Theory of Citizenship for the Age of Globalization, written by Dario Mazzola, challenges traditional notions of citizenship in light of our more interdependent global community. Through a philosophical and historical prism, Mazzola examines the interplay of human rights, freedom, citizenship, and world peace. Citizenship status is usually used to safeguard individual rights in modern citizenship systems, according to this book. This is because these systems are largely founded on the nation-state paradigm. In a world where people are increasingly on the move, migrating across borders, and becoming more connected, this situation poses many problems. Citizenship, as Mazzola points out, is a crucial political institution that establishes individual rights, social recognition, and political participation. This book proposes a more inclusive model of citizenship and discusses the tension between global and national citizenship. This discussion greatly enhances our comprehension of how a more equitable, inclusive, and human rights-oriented political system may be established in this age of globalisation, as well as the prospects for the future of citizenship.